2010
DOI: 10.1016/j.sleep.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Pressure stability with CPAP devices: A bench evaluation

Abstract: The performances of CPAP devices are variable. The device that calibrated for the pressure loss in the circuitry under dynamic conditions and made appropriate pressure adjustments outperformed the other devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…11 Moreover, the additional work of breathing may induce respiratory muscle fatigue and discomfort in patients with acute respiratory failure. 12 With regard to these premises, the majority of devices included in this study may not adequately assist patients because these devices showed a huge fluctuation of the airway pressures around the imposed PEEP level. During the eupneic and tachypneic breathing pattern simulations, the Dimar Easyvent, Deas Flowone, and Superflow showed the lowest pressure swing around the imposed PEEP level, which suggested a better ability to reduce the work of breathing.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, the additional work of breathing may induce respiratory muscle fatigue and discomfort in patients with acute respiratory failure. 12 With regard to these premises, the majority of devices included in this study may not adequately assist patients because these devices showed a huge fluctuation of the airway pressures around the imposed PEEP level. During the eupneic and tachypneic breathing pattern simulations, the Dimar Easyvent, Deas Flowone, and Superflow showed the lowest pressure swing around the imposed PEEP level, which suggested a better ability to reduce the work of breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Since the airflow direction is reversed from exhalation to inhalation it is technically easy to identify the breathing phase and to adjust the pressure correspondingly. Another advantage that the flow transducer offers is it makes it possible to compensate flow loss caused by air leaks, which in turn is helpful in maintaining constant CPAP [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Each experiment was run for 6 h, a period chosen to represent typical nocturnal NPPV use [6]. Control pressure, flow and humidity readings were taken for 20 consecutive steady-state breaths 30 min into the experiment when the humidifier had reached a stable operating temperature.…”
Section: Study Protocolmentioning
confidence: 99%
“…In an attempt to simulate clinical conditions and provide guidance on the likely appearance of tubing condensate, we studied the relationship between room temperature and humidifier setting on tubing condensate formation, pressure delivery and delay in pressure cycling [6][7][8]. The effect of insulating or heating the tubing to reduce tubing condensate formation and subsequent pressure and cycling affects is also examined.…”
Section: Introductionmentioning
confidence: 99%